PEMANFAAATAN TGS 2442 PEMANFAAATAN TGS 2442 UNTUK PENGAMATAN TEMPERATUR GAS CARBONMONOXIDE (CO) PADA LERENG GUNUNG BERAPI MENGGUNAKAN MIKROKONTROLLER: PEMANFAAATAN TGS 2442 UNTUK PENGAMATAN TEMPERATUR GAS CARBONMONOXIDE (CO) PADA LERENG GUNUNG BERAPI MENGGUNAKAN MIKROKONTROLLER - MOHAMMAD IBRAHIM ASHARI,ST, MT ibrahim (JASTEN (Jurnal Aplikasi Sains Teknologi Nasional), 2024)
Through permeable zone detection, we can observe volcanic activity for both mitigation and geothermal exploration. Remote sensing in volcanic areas has the potential to be used to improve our understanding of volcanic processes, to detect volcanic hazard precursor activity, and to provide key monitoring data during volcanic hazard events. Through this research, a tool was created to identify volcanic gas emissions using carbon monoxide gas sensors, temperature sensors, wind speed and wind direction. This equipment can identify changes in quality, temperature and air changes in volcanic mountain environments. The overall test results of the equipment on the temperature sensor rose during the day and fell in the afternoon to evening. The CO gas sensor decreased at 14.00. The wind speed sensor increases starting at 11.00. The wind direction sensor results are random according to the tool test table. It can be concluded that the tool created is functional for remote sensing of the condition of volcanic slopes.